Dissecting the performance of Indian White Leghorn chicken lines through short-term selection experiment - KOUR, ANEET; RAJARAVINDRA, K S; PRINCE, L LESLIE LEO; BHANJA, S K; RAJKUMAR, U (The Indian Journal of Animal Sciences, 2025)
Selection and breeding have resulted in huge genetic gains in White Leghorns over the years. Therefore, it is very important to quantify the rate of genetic progress from time to time. This study was conducted in three selected lines (IWH, IWI and IWK) and one control population (LC) of Indian White Leghorn to understand the short-term effects of selection in the improvement of performance traits. Phenotypic data included production, reproduction and growth traits recorded for five generations starting from 2016 to 2021-22. Using Analysis of Variance, it was revealed that genotype was significantly influencing the generation-wise performance of almost all the traits. IWH was the best performing line for the primary selection trait i.e. egg production at 64 weeks (EP64) over the generations. Genetic response to selection for EP64 was positive in IWH and IWK lines and negative in IWI line. Variance and heritability estimates were also calculated for the egg production (EP) traits from 24 to 72 weeks at four weeks interval in IWH line. Heritability was comparatively higher for the traits at the start of laying cycle (0.191±0.054 for EP24) and decreased considerably towards the end of the laying cycle (0.074±0.06 for EP72). Based on our findings, it is recommended to collate data for few more generations and if negative trend persists in IWI, we can go for either line crossing or introduction of outside variability. Also, genetic parameters can be estimated on a larger dataset in all the lines after few generations for greater precision and accuracy.